Release property study on the novel divalproex sodium enteric-coated capsules - Shuoye Yang; Xin Wang; Jiangsong Jia; Pengyuan Li (Elsevier, 2016)
In the present study, a novel divalproex sodium (DS) enteric-coated capsule was prepared, and high performance liquid chromatography (HPLC) assay method for DS was developed. Their uniformity, release curve and release characteristics in different solvents were examined. The release studies were performed using marketed sample as a reference and data were analyzed in terms of cumulative release amounts as a function of time. It was demonstrated by the results that assay developed was specific, rapid and reliable, which can be used to determine DS in vitro accurately, and our developed samples were similar to reference preparation in in vitro release characteristics. The release characteristics of different batches of samples were quite similar to each other, and the total release percents of DS from enteric-coated capsule were within 0-10% in HCl, and reached close to 100% in phosphate buffer. Similarity factors (f2) of three batches between two preparations were all higher than 50. The developed enteric-coated capsule may be a promising alternative dosage form for treatment of related diseases.